High partial thermal conductivity of luminescence sites: a crucial factor for reducing the heat-induced lowering of the luminescence efficiency. Issue 40 (5th October 2021) - Luo, Ni; Xu, Jing; Cheng, Xiyue; Li, ZhenHua; Huang, Yidong; Whangbo, Myung-Hwan; Deng, Shuiquan; Hong, Maochun
Abstract : The high partial thermal conductivity of luminescence sites is associated with the reduction of the heat-induced lowering of the luminescence efficiency of phosphors. This finding may be helpful for screening efficient phosphors. Abstract : The good thermal stability of a phosphor is crucial for its practical applications. Unfortunately, in the past decades, only the Gurney–Mott equation was available to describe the relation between the luminescence properties of a phosphor and temperature, which is, however, phenomenological and not precise. In this work, we introduced a hypothesis that the lowering of the luminescence efficiency of a phosphor is caused by the heat generated during the luminescence process and can be reduced if the luminescence site dissipates the heat away. We verified this hypothesis by evaluating the thermal conductivities κ of their luminescence sites, the Eu atoms, in the three phosphors, SrLiAl3 N4 :Eu 2+, Sr2 Si5 N8 :Eu 2+ and SrSiN2 :Eu 2+, as well as those of the Sr atoms in their hosts SrLiAl3 N4, Sr2 Si5 N8 and SrSiN2 . It is suggested that our new approach can be employed as a practical criterion to search for phosphor materials with efficient luminescence properties.